THE ROLE OF PUBLIC ADMINISTRATION IN REGULATING THE CONSTRUCTION MATERIALS MARKET OF UZBEKISTAN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The economic liberalization policy pursued in our country serves to implement market principles for the formation of the construction materials market. At the same time, the state uses various forms of state control and regulation. The state must intervene in the regulation of the construction materials market in order to integrate public and personal interests, to develop greater proportions in the economy between savings, consumption and investment based on forecasting, planning strategy, budget financing, tax and other measures.